PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGATHER (NHT )UNTUK MEINGKATKAN HASIL BELAJAR IPA SISWA KELAS IVB SD NEGERI 011 SIDOREJO KECAMATAN SIMPANG KANAN - ', Aspiah; Alpusari, Mahmud; ', Lazim. N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract :The problem this research internal issue is lowering him result of learning IPA class student of IV SDN 011 Sidorejo. With average value only 59,40. this Research target is to improve result learn with applying of model study of type co-operative of Numbered Head Togather ( NHT) executed at 27 March up to 14 April 2014 by 2 cycle. With students amount 25 people, 12 men student people and 13 woman student people, with KKM which have been determined by that is 70. Intrumen data collecting at this skrIPAi is teacher activity sheet, student activity sheet and result learn.. Activity learn in course of study at cycle of I at first meeting is 62,50% with good category mount counted 12,5% hence both meeting becoming 75,00% with good category. At cycle of II activity learn more mount at first meeting is 9,37% hence becoming 84,37% with good category very at both meeting more mount 6,25% becoming 90,62% with good category very. While cycle student activity of I first meeting is 56,25% with natural and enough category of improvement counted 9,37% both meeting becoming 65,62% with good category. At cycle of II first meeting experience of the make-up of counted 12,5% hence becoming 78,12% with natural and good category of improvement at both meeting that is 6,25% becoming 84,37% with good category very. Result learn which obtained from restating value before research with mean 59,40 at cycle of I mount became 69,20 and experience of the make-up of at cycle of II with mean 79,00 Pursuant to research result can be concluded that with applying of type co-operative modelpembelajaran of Numbered Head Togather(NHT) Dapat improve result learn IPA student of SDN 011 Sidorejo.Key words: model learning numbered head togather (NHT) result learn IPA2